On Norms and Agency : Conversations about Gender Equality with Women and Men in 20 Countries - Muñoz Boudet, Ana María; Petesch, Patti; Turk, Carolyn; Thumala, Angélica (Washington, DC: World Bank, 2013)
This report provides tremendous insight on gender norms an area that has been resistant to change, and that constrains achievement of gender equality across many diverse cultures. The report synthesizes data collected from more than 4,000 women and men in 97 communities across 20 countries. It is the largest dataset ever collected on the topic of gender and development, providing an unprecedented opportunity to examine potential patterns across communities on social norms and gender roles, pathways of empowerment, and factors that drive acute inequalities. The analysis raises the profile of persistent social norms and their impact on agency, and catalyzes discourse on the many pathways that create opportunities for women and men to negotiate transformative change. The report is underpinned by the fact that arguably the single most important contribution to development is to unleash the full power of half the people on the planet women. It underscores how crucial making investments in learning, supporting innovations that reduce the time costs of women s mobility, and developing a critical mass of women and men pushing the boundaries of entrenched social norms are in enhancing women s agency and capacity to aspire.